The role of naturally occurring organic compounds in causing soil water repellency. (4th September 2013) - Mainwaring, K.; Hallin, I. L.; Douglas, P.; Doerr, S. H.; Morley, C. P.
Summary: In previous studies, extracts from water‐repellent soils have been applied to wettable substrates to examine the role of organic matter in causing water repellency, but the effects of individual compounds found in water‐repellent soils have not been examined. To address this research gap, acid‐washed sand (AWS) and wettable sandy soil were coated with a range of hydrophobic organic compounds that had been identified by gas chromatography‐mass spectrometry (GC‐MS) analysis of extracts from a range of water‐repellent soils in previous published work. Saturated and unsaturated long chain acids, alkanes, amides, esters, cholesterol and β‐sitosterol were applied at various loadings to investigate the effects of chain length, molecular shape, functional group, heating, particle size and packing efficiency on soil wettability. No single compound induced repellency on AWS at loadings equivalent to the level of detection of individual compounds in water‐repellent soils by GC‐MS. The extent of water repellency induced on AWS varied considerably with compound type, suggesting that it depends more on the presence of specific compounds rather than their quantity. A combination of long chain acid and alkane was found to be the most effective at inducing water repellency. Heating at 105°C for 24 hours caused a marked increase in repellency. Particle size had no effect on degree of induced repellency across the approximately 2.5 times variation in diameter examined.